The History of the Catholic Parish in Miłakowo in the 19th Century - Jodkowski, Marek (Studia Warmińskie, 2014)
The parish priest of Ełdyty Wielkie, Heinrich Renkel (Renze), bought a detached house in Miłakowo on 5th April 1852, with an intention of adapting it for religious purposes. An oratory was organised there and dedicated to the Holy Cross by the parish priest of Ełdyty on 12th December 1855. Since that time, priests from Ełdyty Wielkie occasionally celebrated religious services in it. As a consequence of an increasing number of worshippers, a plot of land was bought in 1864 with an intention of building a church. In the same year, a pastoral institution was created in Miłakowo and the first priest, Augustin Bargel, was appointed. In 1865, Anton Gerigk was appointed as his successor. He launched the implementation of the construction project. The foundation stone of the new temple was laid in 1867. Finally, an aisleless Neogothic church was built. The ceremony of its dedication to the Finding and Exaltation of the Holy Cross, conducted by Bishop Filip Krementz, took place on July 4th 1869. In 1859, a Catholic school was founded in Miłakowo. During the Kulturkampf, the office of a parish priest was vacant in the town. In 1879, 1014 Catholics lived in the parish, and 950 in 1895. The construction of the church buildings and the salaries of the priests and church workers were funded by Catholic associations and organisations, particularly the St. Francis Xavier Society and the St. Boniface and Adalbert Association in Frombork.